2021
DOI: 10.32996/jeltal.2021.3.4.4
|View full text |Cite
|
Sign up to set email alerts
|

A Contrastive Study of Reflexive verbs in English and French

Abstract: This paper describes and compares reflexive verbs in English and French. In collecting the data, a number of books and research works related to the subject have been analysed, using the contrastive method. Results of the analysis indicate that reflexives display a great difference between the two languages. The main observed similarity occurs with the emphatic form. Indeed, the English pronouns “myself”, “himself”, “ourselves” etc, and their French counterparts moi-même, lui-même, nous-mêmes are used in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…There is also a previous study that exposes the differences in grammar between two languages, rather than the similarities. One such study was conducted by Dr. Hafissatou Kane (2021) with the title "A Contrastive Study of Reflexive verbs in English and French". It is found that in English and French reflexive verb cases, the only similarity is only with the empathic form, such as "myself, yourself" in English and "moi-même, toi-même" in French.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a previous study that exposes the differences in grammar between two languages, rather than the similarities. One such study was conducted by Dr. Hafissatou Kane (2021) with the title "A Contrastive Study of Reflexive verbs in English and French". It is found that in English and French reflexive verb cases, the only similarity is only with the empathic form, such as "myself, yourself" in English and "moi-même, toi-même" in French.…”
Section: Introductionmentioning
confidence: 99%